Hydrochemical and Environmental Isotope of Groundwater Samples in Al- Khassa Sub-Basin, Kirkuk, Northeastern Iraq - Al-Kahachi, Shatha A.; Al-Tamimi, Omer S.; Al-Tawash, Balsam S. (Iraqi Journal of Science, 2024)
Hydrochemical study of groundwater has carried out for the Al-Khassa Sub-Basin during the October 2020 and May 2021 seasons for estimating the impacts of seasonal variation and human activity on water quality and using the isotope to determine the main source of recharge. It was found that Biological Oxygen Demand (BOD), Chemical Oxygen Demand  (COD), and Dissolved Oxygen (DO) were out of the standard indicating that the groundwater environment was reduced and difficult to recover from pollution.  Physical and chemical properties that were high (Total Dissolved  Solid (TDS), Total Suspended Solid (TSS),  Electrical conductivity (EC),  Total Hydrocarbon (THC)). Partial pollution by  nitrate and phosphorous due to the use of fertilizers for these elements.  The contamination  by manganese, molybdenum and boron was present in all samples of the two seasons, and partly for lead and mercury due to fertilizers, agricultural activities, the presence of animal and poultry ranches, besides the poor sewage system in the basin based on a septic tank. Washing polluted agricultural soil by rain lead to polluting groundwater. From the environmental isotope analysis (δ2H and δ18O), the isotopic compositions of precipitation were used to construct a local meteoric water line for the study area. The isotopic compositions of groundwater samples were situated to the left of the Global meteoric water line (GMWL), suggesting input of local rainfall that derives from weather front originating from the Mediterranean Sea. Comparing the isotope composition of groundwater and precipitation showed that the infiltrated precipitation that was the main source of recharge to the aquifer system in the study area.